Thermodynamic and Transport Properties of Molten Bi-In Alloys - Singh, B. P.; Singh, B. K.; Jha, I. S.; Shrestha, G. K.; Koirala, I. (Himalayan Physics, 2017)
We have used simple statistical theory to describe the mixing behavior of liquid Bi-In alloys in terms of energetic and structure through the study of their thermodynamic and transport properties. The structural characteristics of Bi-In melts are described by the two microscopic functions, i.e. the concentration fluctuation in long wavelength limit and the Warren-Cowley short range order parameter. The transport properties are analyzed through the diffusion coefficient ratio and viscosity. The Gibb’s free energy of mixing, enthalpy of mixing and entropy of mixing are the thermodynamic functions which are used to describe the thermodynamic behaviors. In whole analysis thermodynamic input parameter, i.e. interchange energy take important role which is temperature dependent. The computed results are in good agreement with experimental data and support a weak ordering tendency in molten Bi-In system. The Himalayan Physics Vol. 6 & 7, April 2017 (5-9)